Assessment of the fracture performance of CR-modified bituminous mixtures enhanced with a reactive polymer using SCB test and image-based crack analysis - Yildirim, Furkan; Kok, Baha Vural; Sengur, Abdulkadir; Ozdemir, Ahmet Munir (Elsevier Sci Ltd, 2026)
Modification of asphalt pavements with various additives has become an inevitable situation in order to resist the increasing traffic conditions and the corrosive effects of the environment for a longer period of time. In this study, the effect of the use of crumb rubber (CR) obtained from waste vehicle tyres in combination with a reactive polymer (B2Last) on fracture performance of bituminous mixtures was investigated by semicircular bending (SCB) test. The performance of CR+B2Last combinations was also compared with the widely used styrene-butadiene-styrene (SBS) modification. This study also examines fracture formation in hot mix asphalt using a U-Net-based image processing approach. It was found that B2Last used with CR realised the polyurethane reaction after short-term aging and was compatible with the bituminous mixture. 8%CR modification showed similar performance with 4% SBS modification, while the use of 2%B2Last in combination with 8%CR significantly increased the effectiveness of CR and offered much better fracture resistance than 4%SBS modification. With the U-net architecture, the crack area and propagation were successfully determined, and it was also found that there was a high correlation between these determined areas and SCB parameters.
Keywords: Crumb rubber; Isocyanate; Modification; Fracture; Image processing